A single point mutation of Ala-25 to Asp in the 14,000-Mr envelope protein of vaccinia virus induces a size change that leads to the small plaque size phenotype of the virus. - Gong, S C (1989)
The molecular defect responsible for a structural and functional abnormality of the 14,000-molecular-weight (14K) envelope protein of vaccinia virus has been identified. Through DNA sequence analysis of the entire 14K gene from wild-type vaccinia virus and three vaccinia virus mutants, a single base change of C to A was found that resulted in the substitution of Asp for Ala-25. This mutation is responsible for protein size abnormality, as documented by cell-free translation in a rabbit reticulocyte lysate of in vitro mRNA transcripts. In addition, through marker rescue experiments we show that this mutation is responsible for the small plaque size phenotype of vaccinia virus mutants. The structural consequence of the point mutation is a possible turn in an alpha-helix domain with destabilization of a hydrophobic interaction at the N terminus, resulting in monomers and trimers of vaccinia virus 14K protein with decreased electrophoretic mobilities. The functional consequence of the point mutation is a reduction in virulence of the virus.